Personality Disorder and Changes in Affect Consciousness: A 3-Year Follow-Up Study of Patients with Avoidant and Borderline Personality Disorder - Normann-Eide, Eivind; Johansen, Merete Selsbakk; Normann-Eide, Tone; Egeland, Jens; Wilberg, Theresa (PLOS ONE, 2015)
Personality disorders (PDs) are highly prevalent in patients receiving psychiatric services, and are associated with significant personal and social costs. Over the past two decades, an increasing number of treatment studies have documented the effectiveness of treatment for patients with PDs, especially when it comes to reduction of symptom distress, risk taking behavior, self-harm, or suicide attempts. However, less is known about the more complex aims of improving the personality structure itself, such as identity- and interpersonal disturbances. Emotional dysfunction is closely associated with PD pathology. The present study investigated changes in affect consciousness (AC) in patients with avoidant or borderline PD, and how these changes were associated with clinical status after 3 years of follow-up. The study included 52 individuals; 79 percent were females, and mean age was 30 years. The evaluations included the Affect Consciousness Interview, Symptom Checklist-90-R, Circumplex of Interpersonal Problems, the Index of Self-Esteem, and three domains (Identity Integration, Relational Capacities, and Self-Control) of the Severity Indices of Personality Problems (SIPP-118). There was a significant increase in the Global AC and AC scores for most of the specific affects from baseline to follow-up. As the present study did not include a control group, it cannot be concluded that changes in AC are effects of psychotherapy, and the possibility of age-related maturation processes cannot be excluded. The change in Global AC contributed significantly to explained variance in the follow-up levels of Circumplex of Interpersonal Problems, and the two SIPP-118 domains Relational Capacities and Identity Integration. Improved AC was not associated with change in the Self-Control domain or the Global Severity Index of Symptom Checklist-90-R. The results suggest that AC may be altered for patients with borderline and avoidant PDs, and this is the first study to report that improvement in AC contribute significantly to the variance in the self- and interpersonal domains of personality functioning.